Evaluating brand personality of Milo towards customers’ brand loyalty / Mohammad Raffi Fhidzon and Muhammad Mawardi Masling - Fhidzon, Mohammad Raffi; Masling, Muhammad Mawardi (2019)
This purpose of this study is to determine the influence of brand personality of Milo towards customers’ brand loyalty. There are several factors in brand personality which are sincerity, excitement, competence, sophistication and ruggedness that influence the loyalty of customers towards Milo. At the same time, this study also focuses on determining the strengths, weaknesses, opportunities and threats faced by Milo brand. Furthermore, strategies that can improve Milo in terms of brand personality for Milo to enhance customers brand loyalty are proposed. The quantitative research is conducted to assess the correlation between the dependent and all the independent variables. The population for this study are consumers of Milo in Petaling Jaya, who are regular customers of this brand. In conducting this study, the sampling technique used is convenience sampling where the most accessible customers are chosen as the subject. Research design involves distributing questionnaire to 100 consumers of Milo product. Our analysis finds that the ANOVA result supported the research hypotheses. Nevertheless, result for the regression analysis of coefficient which is used to test the relationship between brand loyalty and sincerity, excitement, competence, sophistication and ruggedness indicate the strongest influence of competence, sincerity and sophistication of the brand. Thus, based on the outcome of study, sincerity, competence and sophistication are the main brand personalities which can contribute to successful loyalty towards Milo brand.